Kinetic and NMR spectroscopic study of the Chemical Stability and Reaction Pathways of Sugar Nucleotides - Jaakkola Juho; Nieminen Anu; Kivelä Henri; Korhonen Heidi; Tähtinen Petri; Mikkola Satu (Taylor and Francis, 2022)
The alkaline cleavage of two types of sugar nucleotides has been studied by 1H and 31P NMR in order to obtain information on the stability and decomposition pathways in in aqueous solutions under alkaline conditions. The reaction of glucose 1-UDP is straightforward, and products are easy to identify. The results obtained with ribose 5-UDP and ribose 5-phosphate reveal, in contrast, a more complex reaction system than expected, and the identification of individual intermediate species was not possible. Even though definite proof for the mechanisms previously proposed could not be obtained, all the spectroscopic evidence is consistent with them. Results also emphasise the significant effect of conditions, pH, ionic strength and temperature, on the reactivity under chemical conditions.